Characteristics of canopy gap in a broad-leaved mixed forest (Case study: District No. 2, Shast-Kalateh Forest, Golestan province) - Sedigheh Khodaverdi; Mojtaba Amiri; Davoud Kartoolinejad; Jahangir Mohammadi (تحقیقات جنگل و صنوبر ایران, 2018)
Canopy gaps are amongst the most important small-scale phenomena in many temperate, old growth forests, and play a fundamental role in composition and structure of stands. Their occurrence in Hyrcanian forests is associated with numerous effects, including the establishment of species regeneration and increasing forest biodiversity. Due to the importance of in-depth information on canopy gaps, a number of their characteristics were studied in an intact mixed broad-leaved stand in Shast-Kalateh experimental forest Golestan province. We investigated 82 canopy gaps (with a size larger than 40m2) in the compartments 3, 4, 5 and 7 of the forest. For each canopy gap, two parameters of length (L, as the longest distance within the gap) and the width (W, as the largest distance perpendicular to the length) were measured. In addition, data on natural regeneration was sampled within all gaps by species-specific measurement of individuals with DBH 2, with average and median gap size of 470 and 278.6 m2, respectively. The most frequent canopy gaps were those < 400 m2 (71.95%). We observed only few gaps >1000 m2. Most gaps were formed by tree mortality, where hornbeam trees were responsible for 51.45% of gaps. In this study, the increase of gap size to 400 m2 led to increasing the regeneration of tree species. In contrast, the regeneration of main species decreased when gap area increased by more than 500 m2. Hornbeams were the most frequent regenerations in canopy gaps. Finally, the results showed that canopy gaps are crucial factors for regeneration and restoration of forest trees. Therefore, this study calls for increased attention to the different aspects of canopy gaps in order to achieve sustainable management objectives in forestry plans.